5052RC aluminum alloy plate for anodic oxidation and preparation method of 5052RC aluminum alloy plate
By accurately controlling the element content and the ratio of recycling Al in aluminum alloy sheets and optimizing the microstructure, the problem of the defects of the surface of the anodized surface in the high proportion of recycling 5052RC aluminum alloy is solved, and high-quality surface performance and low carbon emissions are achieved.
Patent Information
- Application Number
- CN202411873519.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
AI Technical Summary
Due to the increase in Fe element content in the high proportion of recycling material 5052RC aluminum alloy, the surface is prone to heterochromatic stripes defects after anodization treatment, which affects the appearance quality.
By accurately controlling the content of Si, Fe, Cu, Mn, Mg, Cr, Zn and Ti elements in aluminum alloy sheets, and controlling the proportion of recovered Al elements to be no less than 50%, the microstructure of aluminum alloys can be optimized and surface defects can be reduced. Specific steps include smelting, semi-continuous casting, homogenizing heat treatment, hot rolling, cold rolling and annealing treatment.
The surface quality of aluminum alloy sheets has been significantly improved, making its brightness L value exceed 92.5, the color difference ΔE value is less than 0.1, and there are no different color stripe defects, meeting the high standard needs of high-end applications, and at the same time reducing the carbon emissions of the materials, promoting environmental protection and sustainable development.
Smart Images

Figure CN119736526A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloy materials, and in particular to a 5052RC aluminum alloy plate for anodizing and a preparation method thereof. Background Art
[0002] With the proposal of the goal of low-carbon development of my country's industry, enterprises in industries such as automobiles, packaging and consumer electronics are increasingly inclined to purchase materials with low carbon emissions. In the 3C electronic products industry, the demand for low-carbon and recycled materials is particularly prominent. The aluminum industry has become one of the important goals of carbon emission reduction in the industrial field due to its high energy consumption and high carbon emissions in the production process. In recent years, high-end low-carbon aluminum alloy new materials with recycled aluminum as raw materials have gradually become a development trend, especially in the 5000 series aluminum materials. This series of aluminum materials has good strength, rigidity and formability, is suitable for the production of plates and strips of different thicknesses, and has excellent anodizing performance, which can meet the high-tech requirements of 3C products for appearance and decorative performance.
[0003] However, with the increase in the proportion of recycled materials, the increase in the Fe content in 5000 series aluminum materials leads to the appearance of heterochromatic streaks on the surface after anodizing, thus affecting the appearance quality. In order to continue to use a high proportion of recycled aluminum while reducing carbon emissions and ensure the quality of the aluminum alloy surface after anodizing, it is urgent to develop a 5000 series anodized aluminum material suitable for high proportion of recycled materials, so that the product has excellent surface properties and an appearance without heterochromatic streaks. Summary of the invention
[0004] The main purpose of the present invention is to provide a 5052RC aluminum alloy plate for anodizing and a preparation method thereof, so as to solve the problem in the prior art that the high proportion of recycled material 5052RC aluminum alloy has an increased Fe content, which leads to the defect of different color stripes on the surface after anodizing treatment, thus affecting the appearance quality.
[0005] To achieve the above object, according to one aspect of the present invention, a 5052RC aluminum alloy plate for anodizing is provided, wherein the 5052RC aluminum alloy plate for anodizing comprises, by mass percentage, 0.1-0.3% of Si element, 0.15-0.45% of Fe element, 0.05-0.20% of Cu element, 1.0-1.5% of Mn element, 2.2-2.8% of Mg element, 0.15-0.35% of Cr element, ≤0.1% of Zn element and ≤0.03% of Ti element, and the remainder is Al and unavoidable impurities, wherein Al includes recycled Al, and the proportion of recycled Al in the 5052RC aluminum alloy plate for anodizing is ≥50%; wherein the surface brightness L value of the 5052RC aluminum alloy plate for anodizing is greater than 92.5, the color difference ΔE value is less than 0.1, and there is no heterochromatic streak defect.
[0006] Furthermore, the average grain size of the above-mentioned 5052RC aluminum alloy plate for anodization is 15 μm to 25 μm; and / or, the 5052RC aluminum alloy plate for anodization includes Cube textured grains, and the area proportion of Cube textured grains in the 5052RC aluminum alloy plate for anodization is 5% to 15%; and / or the number density of the second phase in the 5052RC aluminum alloy plate for anodization is ≥1.0×10 3 Pieces / mm 2 , the maximum size of the second phase in 5052RC aluminum alloy sheet for anodizing is ≤10μm.
[0007] Furthermore, the electrical conductivity of the 5052RC aluminum alloy plate for anodizing is 23.3-23.6 mS / m.
[0008] According to another aspect of the present invention, a method for preparing the aforementioned 5052RC aluminum alloy plate for anodizing is provided, the preparation method comprising a smelting step, a semi-continuous casting step, a homogenization heat treatment step, a hot rolling step, a multiple cold rolling step and an annealing step performed in sequence, characterized in that the temperature of the homogenization heat treatment step is 520-580°C, the heating rate of the homogenization heat treatment step is ≤50°C / h, and the time of the homogenization heat treatment step is 2-5h.
[0009] Furthermore, the temperature of the homogenization heat treatment step is 570-580° C.; and / or the average grain size of the ingot after the homogenization heat treatment step is 150 μm-190 μm.
[0010] Furthermore, an Al3Fe phase exists during the above-mentioned homogenization heat treatment step, and after the homogenization heat treatment step, the Al3Fe phase gradually changes from a fishbone-shaped Al3Fe phase to a short rod-shaped Al3Fe phase; and / or, the average size of the Al3Fe phase is between 10 and 50 μm, and the area ratio is less than 1.8%; and / or, the average size of the fishbone-shaped Al3Fe phase is 5 to 10 μm.
[0011] Furthermore, during the homogenization heat treatment step, an Al6Mn phase exists, and after the homogenization heat treatment step, an average size of the Al6Mn phase is between 0.1 and 1.0 μm, and an area ratio of less than 0.1%.
[0012] Furthermore, a primary Mg2Si phase is generated in the initial process of the above-mentioned homogenization heat treatment step, and in the intermediate process of the homogenization heat treatment step, the primary Mg2Si phase is gradually spheroidized and dissolved back into the aluminum alloy matrix to form a Mg2Si dispersed phase. After the homogenization heat treatment step, the average size of the Mg2Si dispersed phase is between 3 and 10 μm, and the area share is less than 0.1%.
[0013] Furthermore, the total cold rolling rate of the above multiple cold rolling steps is 90-95%.
[0014] Furthermore, the annealing temperature in the above annealing step is 280-320° C., and the holding time is 2-5 hours.
[0015] By applying the technical solution of the present invention, the present application discloses a 5052RC aluminum alloy sheet for anodizing. By precisely controlling the contents of Si, Fe, Cu, Mn, Mg, Cr, Zn and Ti elements in the aluminum alloy sheet, and controlling the proportion of recycled Al elements to be not less than 50%, the microstructure of the aluminum alloy can be optimized, surface defects can be reduced, and its surface quality can be significantly improved. At the same time, its brightness L value exceeds 92.5, the color difference ΔE value is less than 0.1, and no heterochromatic strip defects are generated. The above aluminum alloy sheet and strip with excellent surface performance of the present application can better meet the high standard requirements of high-end applications such as 3C products. At the same time, due to the use of a high proportion of recycled aluminum, the carbon emission of the material is reduced, environmental protection and sustainable development are promoted, and it has significant economic value and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The morphology and distribution diagram of the Al3Fe phase and the Mg2Si phase in the 5052RC aluminum alloy ingot of Example 1 of the present application are shown;
[0018] Figure 2 The morphology and distribution diagram of the Al3Fe phase and the Mg2Si phase in the 5052RC aluminum alloy ingot of Example 2 of the present application are shown;
[0019] Figure 3 The morphology and distribution diagram of the Al3Fe phase and the Mg2Si phase in the 5052RC aluminum alloy ingot of Example 3 of the present application are shown;
[0020] Figure 4 The morphology and distribution diagram of the Al3Fe phase in the 5052RC aluminum alloy sheet and strip for anodization of Comparative Example 1 of the present application are shown;
[0021] Figure 5 The morphology and distribution diagram of the Mg2Si phase in the 5052RC aluminum alloy sheet and strip for anodization of Comparative Example 1 of the present application are shown;
[0022] Figure 6The figure shows the grain size distribution and the Cube texture area ratio in the 5052RC aluminum alloy plate for anodization in Example 1 of the present application;
[0023] Figure 7 The diagram shows the distribution of the second phase in the 5052RC aluminum alloy sheet for anodization in Example 1 of the present application. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0025] As analyzed in the background technology of the present application, in the prior art, the high-proportion recycled material 5052RC aluminum alloy has an increase in the Fe element content, which leads to the defect of different-color stripes on the surface after anodizing treatment, thereby affecting the appearance quality. In order to solve the above problem, the present application provides a 5052RC aluminum alloy plate for anodizing and a preparation method thereof.
[0026] In a typical embodiment of the present application, a 5052RC aluminum alloy sheet for anodizing is provided, wherein the 5052RC aluminum alloy sheet for anodizing comprises, by mass percentage, 0.1-0.3% of Si element, 0.15-0.45% of Fe element, 0.05-0.20% of Cu element, 1.0-1.5% of Mn element, 2.2-2.8% of Mg element, 0.15-0.35% of Cr element, ≤0.1% of Zn element and ≤0.03% of Ti element, and the rest is Al and unavoidable impurities, wherein Al includes recycled Al, and the proportion of recycled Al in the 5052RC aluminum alloy sheet for anodizing is ≥50%; wherein the surface brightness L value of the 5052RC aluminum alloy sheet for anodizing is greater than 92.5, the color difference ΔE value is less than 0.1, and there is no heterochromatic streak defect.
[0027] The present application discloses a 5052RC aluminum alloy sheet for anodizing. By precisely controlling the contents of Si, Fe, Cu, Mn, Mg, Cr, Zn and Ti elements in the aluminum alloy sheet and controlling the proportion of recycled Al elements to be not less than 50%, the microstructure of the aluminum alloy can be optimized, surface defects can be reduced, and the surface quality can be significantly improved. At the same time, the brightness L value exceeds 92.5, the color difference ΔE value is less than 0.1, and no heterochromatic strip defects are generated. The above aluminum alloy sheet and strip with excellent surface performance of the present application can better meet the high standard requirements of high-end applications such as 3C products. At the same time, due to the use of a high proportion of recycled aluminum, the carbon emission of the material is reduced, environmental protection and sustainable development are promoted, and it has significant economic value and environmental benefits.
[0028] In one embodiment of the present application, the average grain size of the above-mentioned 5052RC aluminum alloy plate for anodization is 15 μm to 25 μm; and / or, the 5052RC aluminum alloy plate for anodization includes Cube textured grains, and the area proportion of Cube textured grains in the 5052RC aluminum alloy plate for anodization is 5% to 15%; and / or the number density of the second phase in the 5052RC aluminum alloy plate for anodization is ≥1.0×10 3 Pieces / mm 2 , the maximum size of the second phase in 5052RC aluminum alloy sheet for anodizing is ≤10μm.
[0029] Preferably, the texture in the 5052RC aluminum alloy sheet for anodizing, the average grain size in the 5052RC aluminum alloy sheet for anodizing, the Cube texture grains and their area ratio, the number density and the maximum size of the second phase are controlled within the above ranges, which can effectively reduce the internal stress and optimize the microstructure of the aluminum alloy sheet, thereby helping to improve the mechanical properties and processing properties of the aluminum alloy sheet, and further facilitate the aluminum alloy sheet to maintain good stability during subsequent heat treatment, hot rolling and cold rolling processes, thereby improving the comprehensive performance of the aluminum alloy sheet.
[0030] In one embodiment of the present application, the electrical conductivity of the 5052RC aluminum alloy plate for anodizing is 23.3-23.6 mS / m.
[0031] The conductivity of the material is affected by its microstructure and the distribution of the second phase. Controlling the conductivity of 5052RC aluminum alloy sheet for anodizing within the above range reflects the electrical conductivity and processing performance of the aluminum alloy sheet to a certain extent, which is particularly important for the connection and signal transmission of electronic products.
[0032] In another typical embodiment of the present application, a method for preparing the above-mentioned 5052RC aluminum alloy plate for anodizing is provided, the preparation method comprising a smelting step, a semi-continuous casting step, a homogenization heat treatment step, a hot rolling step, a multiple cold rolling step and an annealing step performed in sequence, the temperature of the homogenization heat treatment step is 520-580°C, the heating rate of the homogenization heat treatment step is ≤50°C / h, and the time of the homogenization heat treatment step is 2-5h.
[0033] The present application provides a method for preparing the above-mentioned 5052RC aluminum alloy sheet for anodizing, with the focus on the homogenization heat treatment step. The homogenization heat treatment is carried out at a lower heating rate, which is conducive to the uniform diffusion of elements and avoids the rapid growth of grains, thereby optimizing the distribution of the second phase and improving the surface treatment performance and conductivity of the aluminum alloy material. Therefore, by controlling the temperature and heating rate of the homogenization heat treatment step, it is helpful to significantly improve the microstructure and performance of the aluminum alloy sheet. Thereby avoiding the problem of the easy appearance of heterochromatic streaks on the surface after anodizing treatment due to the increase of Fe element content in the high-proportion recycled material 5052RC aluminum alloy.
[0034] In one embodiment of the present application, the temperature of the homogenization heat treatment step is 570-580° C.; and / or, the average grain size of the ingot after the homogenization heat treatment step is 150 μm-190 μm.
[0035] The increase in temperature helps promote the growth of grains and the dissolution of the second phase, but too high a temperature can easily lead to excessive grain growth, reducing the strength and surface quality of the aluminum alloy. Therefore, by further optimizing the temperature of the homogenization heat treatment and controlling the average grain size within the above range, it is beneficial to improve the uniformity and processing performance of the aluminum alloy material, while also helping to reduce the adverse effects of excessive grain size.
[0036] In one embodiment of the present application, an Al3Fe phase exists during the above-mentioned homogenization heat treatment step, and after the homogenization heat treatment step, the Al3Fe phase gradually transforms from a fishbone-shaped Al3Fe phase to a short rod-shaped Al3Fe phase; and / or, the average size of the Al3Fe phase is between 10 and 50 μm, and the area ratio is less than 1.8%; and / or, the average size of the fishbone-shaped Al3Fe phase is 5 to 10 μm.
[0037] The Al3Fe phase will show different morphologies under different heat treatment conditions. The fishbone-shaped Al3Fe phase is prone to color difference during anodization. By adjusting the heat treatment conditions, the Al3Fe phase can be transformed from a fishbone-shaped phase to a short rod-shaped phase with smaller size and more uniform distribution, thereby reducing surface defects. It is preferred to control the relevant parameters of the Al3Fe phase within the above range, which is more conducive to reducing the risk of generating heterochromatic stripes and improving the surface brightness and color difference uniformity.
[0038] In one embodiment of the present application, an Al6Mn phase exists during the above-mentioned homogenization heat treatment step, and after the homogenization heat treatment step, the average size of the Al6Mn phase is between 0.1 and 1.0 μm, and the area ratio is less than 0.1%.
[0039] The treatment of Al6Mn phase is similar to that of Al3Fe phase, but more emphasis is placed on its transformation and size control during heat treatment. Appropriate heat treatment conditions can promote the uniform distribution and size control of Al6Mn phase and reduce the adverse effects on surface treatment. Therefore, by controlling the parameters such as the morphology and size of the Al6Mn phase within the above range, the microstructure of the aluminum alloy sheet can be further optimized, potential surface treatment defects can be reduced, and its overall performance can be improved.
[0040] In one embodiment of the present application, a primary Mg2Si phase is generated in the initial process of the above-mentioned homogenization heat treatment step, and in the intermediate process of the homogenization heat treatment step, the primary Mg2Si phase is gradually spheroidized and dissolved back into the aluminum alloy matrix to form a Mg2Si dispersed phase. After the homogenization heat treatment step, the average size of the Mg2Si dispersed phase is between 3 and 10 μm, and the area share is less than 0.1%.
[0041] The primary Mg2Si phase is optimized during the homogenization heat treatment process. Through spheroidization and dissolution, the final Mg2Si dispersed phase can reduce the hard points at the grain boundaries and improve the plasticity and conductivity of the material. By further controlling the average grain size and area ratio of the Mg2Si dispersed phase within the above range, it is more helpful to improve the conductivity and surface treatment quality of the aluminum alloy material.
[0042] In one embodiment of the present application, the total cold rolling rate of the above-mentioned multiple cold rolling steps is 90-95%.
[0043] By controlling the total cold rolling rate during the cold rolling process, it is beneficial to adjust the thickness and microstructure of the aluminum alloy sheet. The appropriate cold rolling rate can enhance the mechanical properties of the aluminum alloy sheet, making it more suitable for subsequent processing and application. Therefore, by controlling the total cold rolling rate within the above range, it is beneficial to improve the thickness and dimensional accuracy of the aluminum alloy material, and at the same time, it is also beneficial to improve the strength and hardness of the aluminum alloy sheet.
[0044] In one embodiment of the present application, the annealing temperature in the above annealing step is 280-320° C., and the holding time is 2-5 hours.
[0045] Annealing is a method of heating the alloy sheet to a certain temperature and keeping it warm for a period of time to repair the lattice defects in the material, eliminate work hardening, and thus improve the formability and surface quality of the sheet. Therefore, by controlling the temperature and holding time of the annealing step within the above range, the microstructure of the material can be further stabilized, internal stress can be eliminated, and the formability and surface treatment performance of the aluminum alloy sheet can be improved.
[0046] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0047] Example 1
[0048] The recycled aluminum accounts for 60% of the 5052RC aluminum alloy sheet for anodizing. The raw materials are composed of the following components in weight percentage: Si = 0.2%, Fe = 0.2%, Cu = 0.1%, Mn = 1.3%, Mg = 2.5%, Cr = 0.2%, Zn = 0.05%, Ti = 0.01%, and the balance of Al and unavoidable impurities;
[0049] The components of the aluminum alloy raw materials with the above mass percentages were weighed respectively, smelted, and then prepared into 5052RC aluminum alloy ingots by semi-continuous casting. The morphology and distribution of the Al3Fe phase and Mg2Si phase are shown in FIG. Figure 1 As shown;
[0050] The heating rate was controlled to be 50°C / h, and the 5052RC aluminum alloy ingot was heated from room temperature to 520°C, and then the 5052RC aluminum alloy ingot was subjected to homogenization heat treatment and kept at this temperature for 4 hours, so that the Mg2Si phase in the alloy was completely dissolved back into the matrix;
[0051] The 5052RC aluminum alloy ingot is hot rolled to produce a hot rolled plate with a thickness of 12 mm;
[0052] The hot-rolled sheet is subjected to four cold rolling processes, and the total cold rolling rate after the four cold rolling processes is controlled to be 90%, thereby obtaining a cold-rolled sheet;
[0053] The cold rolled sheet was annealed at 300°C for 2 h, and finally an anodized 5052RC aluminum alloy sheet with a conductivity of 23.3MS / m was obtained. The number density of the second phase in the anodized 5052RC aluminum alloy sheet was 7.8×10 3 Pieces / mm 2 The maximum size of the second phase is ≤10μm. The grain size distribution and the proportion of the Cube texture area in the 5052RC aluminum alloy sheet for anodization are shown in the figure below. Figure 6 As shown in the figure, the distribution of the second phase in the 5052RC aluminum alloy sheet for anodizing is shown in Figure 7 shown.
[0054] Surface performance after anodizing: brightness L value is 92.8, color difference ΔE is 0.09, and there is no obvious color streak defect.
[0055] Example 2
[0056] The recycled aluminum in the 5052RC aluminum alloy sheet for anodizing accounts for 65%, and the raw materials are composed of the following components in weight percentage: Si = 0.1%, Fe = 0.3%, Cu = 0.15%, Mn = 1.1%, Mg = 2.3%, Cr = 0.25%, Zn = 0.08%, Ti = 0.02%, and the balance of Al and unavoidable impurities;
[0057] The components of the aluminum alloy raw materials with the above mass percentages were weighed respectively, smelted, and then prepared into 5052RC aluminum alloy ingots by semi-continuous casting. The morphology and distribution of the Al3Fe phase and Mg2Si phase are shown in FIG. Figure 2 As shown;
[0058] The heating rate was controlled to be 50°C / h, and the 5052RC aluminum alloy ingot was heated from room temperature to 540°C, and then the 5052RC aluminum alloy ingot was subjected to homogenization heat treatment and kept at this temperature for 6 hours, so that the Mg2Si phase in the alloy was completely dissolved back into the matrix;
[0059] The 5052RC aluminum alloy ingot is hot rolled to produce a hot rolled plate with a thickness of 12 mm;
[0060] The hot-rolled sheet is subjected to four cold rolling processes, and the total cold rolling rate after the four cold rolling processes is controlled to be 90%, thereby obtaining a cold-rolled sheet;
[0061] The cold rolled sheet was annealed at 300°C for 3 hours, and finally an anodized 5052RC aluminum alloy sheet with a conductivity of 23.5MS / m was obtained.
[0062] Surface performance after anodizing: brightness L value is 93.0, color difference ΔE is 0.07, and there is no color streak defect.
[0063] Example 3
[0064] The recycled aluminum accounts for 70% of the 5052RC aluminum alloy sheet for anodizing. The raw materials are composed of the following components in weight percentage: Si = 0.3%, Fe = 0.4%, Cu = 0.2%, Mn = 1.5%, Mg = 2.8%, Cr = 0.25%, Zn = 0.1%, Ti = 0.03%, and the balance of Al and unavoidable impurities;
[0065] The components of the aluminum alloy raw materials with the above mass percentages were weighed respectively, smelted, and then prepared into 5052RC aluminum alloy ingots by semi-continuous casting. The morphology and distribution of the Al3Fe phase and Mg2Si phase are shown in FIG. Figure 3 As shown;
[0066] The heating rate is controlled to be 50°C / h, and the 5052RC aluminum alloy ingot is heated from room temperature to 580°C, and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment and kept at this temperature for 8 hours, so that the Mg2Si phase in the alloy is completely dissolved back into the matrix;
[0067] The 5052RC aluminum alloy ingot is hot rolled to produce a hot rolled plate with a thickness of 12 mm;
[0068] The hot-rolled sheet is subjected to four cold rolling processes, and the total cold rolling rate after the four cold rolling processes is controlled to be 90%, thereby obtaining a cold-rolled sheet;
[0069] The cold rolled sheet was annealed at 300°C for 3 hours to obtain anodized 5052RC aluminum alloy sheet.
[0070] Surface performance after anodizing: brightness L value is 93.3, color difference ΔE is 0.05, and there is no color streak defect.
[0071] Example 4
[0072] The difference from Example 1 is that the heating rate is controlled to be 50°C / h, the 5052RC aluminum alloy ingot is heated from room temperature to 550°C, and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0073] Example 5
[0074] The difference from Example 1 is that the heating rate is controlled to be 50° C. / h, the 5052RC aluminum alloy ingot is heated from room temperature to 580° C., and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0075] Example 6
[0076] The difference from Example 1 is that the heating rate is controlled to be 50°C / h, the 5052RC aluminum alloy ingot is heated from room temperature to 570°C, and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0077] Example 7
[0078] The difference from Example 1 is that the heating rate is controlled to be 10° C. / h, so that the 5052RC aluminum alloy ingot is heated from room temperature to 520° C., and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0079] Example 8
[0080] The difference from Example 1 is that the hot rolled sheet is subjected to four cold rolling treatments, and the total cold rolling rate after the four cold rolling treatments is controlled to be 92.5%, and finally a 0.9 mm 5052RC aluminum alloy sheet for anodizing is obtained.
[0081] Example 9
[0082] The difference from Example 1 is that the hot rolled sheet is subjected to four cold rolling treatments, and the total cold rolling rate after the four cold rolling treatments is controlled to be 93%, and finally a 0.8 mm 5052RC aluminum alloy sheet for anodizing is obtained.
[0083] Example 10
[0084] The difference from Example 1 is that the hot-rolled sheet is subjected to three cold rolling treatments, and the total cold rolling rate after the three cold rolling treatments is controlled to be 83.33%, and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0085] Embodiment 11
[0086] The difference from Example 1 is that the cold rolled sheet is annealed at 290° C. to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0087] Example 12
[0088] The difference from Example 1 is that the cold-rolled sheet is annealed at 310° C. to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0089] Embodiment 13
[0090] The difference from Example 1 is that the cold-rolled sheet is annealed at 260° C. to finally obtain a 5052RC aluminum alloy sheet for anodizing.
[0091] Embodiment 14
[0092] The difference from Example 1 is that the holding time during the annealing process is 3 hours, and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0093] Embodiment 15
[0094] The difference from Example 1 is that the holding time during the annealing process is 4 hours, and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0095] Comparative Example 1
[0096] The difference from Example 1 is that the heating rate is controlled to be 50°C / h, the 5052RC aluminum alloy ingot is heated from room temperature to 500°C, and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment and kept warm for 6 hours to finally obtain a 5052RC aluminum alloy sheet for anodizing, wherein the morphology and distribution diagram of the Al3Fe phase in the 5052RC aluminum alloy sheet and strip for anodizing are shown in Figure 4, and the morphology and distribution diagram of the Mg2Si phase in the 5052RC aluminum alloy sheet and strip for anodizing are shown in Figure 5.
[0097] Comparative Example 2
[0098] The difference from Example 1 is that the heating rate is controlled to be 50°C / h, the 5052RC aluminum alloy ingot is heated from room temperature to 600°C, and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment and kept warm for 4 hours, and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0099] Comparative Example 3
[0100] The difference from Example 1 is that the temperature of the 5052RC aluminum alloy ingot is raised from room temperature to 540° C., and then the 5052RC aluminum alloy ingot is subjected to homogenization heat treatment and kept at this temperature for 1 hour, so as to finally obtain a 5052RC aluminum alloy sheet for anodization.
[0101] Comparative Example 4
[0102] The difference from Example 1 is that the heating rate is controlled to be 60° C. / h, and finally a 5052RC aluminum alloy sheet for anodizing is obtained.
[0103] Performance Test:
[0104] The relevant parameters of the Al3Fe phase, Mg2Si dispersed phase and Al6Mn phase after homogenization heat treatment of the above embodiments and comparative examples were tested respectively, and the test results are listed in Table 1.
[0105] Average grain size of 5052RC aluminum alloy ingot: GB / T 6394-2002;
[0106] The average size of Al3Fe phase, the average size of Mg2Si dispersed phase, and the average size of Al6Mn phase: GB / T 3246.1-2012;
[0107] Electrical conductivity of 5052RC aluminum alloy sheet: GB / T 12966-2008;
[0108] Surface brightness L value, color difference ΔE: GB / T12967.6-2008.
[0109] The test methods for the area ratio of Al3Fe phase, the area ratio of Mg2Si dispersed phase, and the area ratio of Al6Mn phase are as follows:
[0110] 1. Sample Preparation
[0111] (1) Cutting
[0112] Cut small pieces of aluminum alloy ingots or heat-treated samples with a suitable size of about 10*10mm to avoid structural changes caused by mechanical stress.
[0113] (2) Mounting and polishing
[0114] The sample was embedded in epoxy resin and subjected to rough grinding, fine grinding and polishing according to the metallographic sample preparation method. After final polishing, the surface achieved a mirror effect.
[0115] 2. Microscopic observation and composition verification
[0116] (1) Scanning electron microscopy (SEM)
[0117] Use SEM for high magnification observation to distinguish different secondary phases and dispersed phases, often combined with backscattered electron (BSE) imaging to obtain the brightness difference of different phases:
[0118] Al3Fe phase, usually brighter, with short rod or fishbone morphology;
[0119] Mg2Si dispersed phase, relatively dark, distributed in spherical or granular form;
[0120] Al6Mn phase, brighter, granular or irregular shape.
[0121] (2) Energy dispersive spectrometry (EDS)
[0122] EDS is used to perform qualitative or quantitative composition analysis on different phase regions to confirm the location and characteristics of the Al3Fe phase, Mg2Si dispersion, and Al6Mn phase.
[0123] 3. Image Analysis and Area Ratio Determination
[0124] (1) Microscopic image acquisition
[0125] In the identified areas, high-resolution images are taken using an optical microscope or SEM to ensure that the distribution of each phase is clearly visible on the sample surface.
[0126] (2) Image processing
[0127] Use image analysis software (such as ImageJ) to process the collected images:
[0128] Step 1: Grayscale processing to separate different phases according to their brightness differences;
[0129] Step 2: Threshold segmentation to extract the target phase (such as Al3Fe phase, Mg2Si dispersion, Al6Mn phase) from the matrix;
[0130] Step 3: Fill and denoise to clean up isolated noise points and artifacts;
[0131] Step 4: Count the area pixels of the target phase.
[0132] (3) Calculation of area ratio
[0133] Calculate the area ratio using the formula:
[0134] Area ratio (%) = target phase pixel area\total pixel area*100%
[0135] The measurement results of multiple fields of view were averaged to reduce the impact of sample inhomogeneity on the data.
[0136] The average grain size of the 5052RC aluminum alloy ingot obtained in the above examples and comparative examples, the conductivity, surface brightness L value, color difference ΔE of the 5052RC aluminum alloy plate after anodization, and the test results of whether the product is qualified are listed in Table 2.
[0137] Table 1
[0138]
[0139]
[0140] Table 2
[0141]
[0142]
[0143] Note: OK means the product is qualified, NG means the product is unqualified.
[0144] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0145] The present application discloses a 5052RC aluminum alloy sheet for anodizing. By precisely controlling the contents of Si, Fe, Cu, Mn, Mg, Cr, Zn and Ti elements in the aluminum alloy sheet and controlling the proportion of recycled Al elements to be not less than 50%, the microstructure of the aluminum alloy can be optimized, surface defects can be reduced, and the surface quality can be significantly improved. At the same time, the brightness L value exceeds 92.5, the color difference ΔE value is less than 0.1, and no heterochromatic strip defects are generated. The above aluminum alloy sheet and strip with excellent surface performance of the present application can better meet the high standard requirements of high-end applications such as 3C products. At the same time, due to the use of a high proportion of recycled aluminum, the carbon emission of the material is reduced, environmental protection and sustainable development are promoted, and it has significant economic value and environmental benefits.
[0146] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A 5052RC aluminum alloy sheet for anodizing, characterized in that: The 5052RC aluminum alloy sheet for anodizing comprises, by mass percentage, 0.1-0.3% of Si element, 0.15-0.45% of Fe element, 0.05-0.20% of Cu element, 1.0-1.5% of Mn element, 2.2-2.8% of Mg element, 0.15-0.35% of Cr element, ≤0.1% of Zn element and ≤0.03% of Ti element, and the rest is Al and unavoidable impurities, wherein the Al comprises recycled Al, and the recycled Al accounts for ≥50% of the 5052RC aluminum alloy sheet for anodizing; wherein the surface brightness L value of the 5052RC aluminum alloy sheet for anodizing is greater than 92.5, the color difference ΔE value is less than 0.1, and there is no heterochromatic streak defect.
2. The 5052RC aluminum alloy sheet for anodizing according to claim 1, characterized in that: The average grain size of the 5052RC aluminum alloy plate for anodization is 15 μm to 25 μm; and / or the 5052RC aluminum alloy plate for anodization includes Cube textured grains, and the area proportion of the Cube textured grains in the 5052RC aluminum alloy plate for anodization is 5% to 15%; and / or the number density of the second phase in the 5052RC aluminum alloy plate for anodization is ≥1.0×10 3 Pieces / mm 2 The maximum size of the second phase in the anodized 5052RC aluminum alloy sheet is ≤10 μm.
3. The 5052RC aluminum alloy sheet for anodizing according to claim 1 or 2, characterized in that: The electrical conductivity of the 5052RC aluminum alloy plate for anodizing is 23.3-23.6 mS / m.
4. A method for preparing the 5052RC aluminum alloy plate for anodization according to any one of claims 1 to 3, the method comprising a smelting step, a semi-continuous casting step, a homogenization heat treatment step, a hot rolling step, a multiple cold rolling step and an annealing step performed in sequence, characterized in that: The temperature of the homogenization heat treatment step is 520-580° C., the heating rate of the homogenization heat treatment step is ≤50° C. / h, and the time of the homogenization heat treatment step is 2-5h.
5. The preparation method according to claim 4, characterized in that: The temperature of the homogenization heat treatment step is 570-580° C.; and / or the average grain size of the ingot after the homogenization heat treatment step is 150 μm-190 μm.
6. The preparation method according to claim 4 or 5, characterized in that: During the homogenization heat treatment step, an Al3Fe phase exists, and after the homogenization heat treatment step, the Al3Fe phase gradually transforms from a fishbone-shaped Al3Fe phase to a short rod-shaped Al3Fe phase; and / or, the average size of the Al3Fe phase is between 10 and 50 μm, and the area ratio is less than 1.8%; And / or, the average size of the fishbone-shaped Al3Fe phase is 5 to 10 μm.
7. The preparation method according to any one of claims 4 to 6, characterized in that: During the homogenization heat treatment step, an Al6Mn phase exists, and after the homogenization heat treatment step, the average size of the Al6Mn phase is between 0.1 and 1.0 μm, and the area ratio is less than 0.1%.
8. The preparation method according to any one of claims 4 to 7, characterized in that A primary Mg2Si phase is generated in the initial process of the homogenization heat treatment step. In the intermediate process of the homogenization heat treatment step, the primary Mg2Si phase is gradually spheroidized and dissolved back into the aluminum alloy matrix to form a Mg2Si dispersed phase. After the homogenization heat treatment step, the average size of the Mg2Si dispersed phase is between 3 and 10 μm, and the area ratio is less than 0.1%.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The total cold rolling rate of the multiple cold rolling steps is 90-95%.
10. The preparation method according to any one of claims 4 to 9, characterized in that: The annealing temperature in the annealing step is 280-320° C., and the insulation time is 2-5 hours.